MOBILISASI MASSA KEMENANGAN KOLOM KOSONG PADA PEMILIHAN WALIKOTA MAKASSAR TAHUN 2018 - Kambo, Gustiana (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2021)
The study aims to describe the winning of the blank box in Makassar Mayoral Election in 2018. This research used a qualitative method specifically case study to analyze the mass direction pattern in the victory of blank box. By using the Huntington concept of mobilization and mass communication from Philip Tichenor, the study found that the victory of the blank box was caused by means of intense direct and indirect mass mobilization. In an indirect way, this mobilization used the power of social media, Facebook, the success team and volunteers to formulate information and messages that are deliberately carried out for to attract the attention of voters.